High-strength concrete and preparation method thereof

Through the combination of materials and modification treatment with specific ratios, the strength, durability and crack resistance of concrete are improved, the problem of insufficient performance of traditional concrete is solved, and high-strength, low-cost and low-complexity preparation is achieved. It is suitable for modern times Construction demand.

CN119219382APending Publication Date: 2024-12-31FUJIAN ZHUOYUE CONSTR ENG DEV CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411340614.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Traditional concrete has shortcomings in strength, durability and crack resistance, and the preparation process and cost control of high-strength concrete are difficult to meet the high requirements of modern building materials.

Method used

Using specific proportions of combined materials, including cement, modified glass microbeads, aggregates, fly ash, calcium hydroxide, reinforced fibers and expanded fillers, the strength, durability and Resistant cracking performance and reduce costs.

Benefits of technology

It achieves high strength, low density, excellent durability and crack resistance, reduces temperature cracks, is suitable for strict engineering applications, and reduces preparation complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059575850000101
    Figure BDA0005059575850000101
Patent Text Reader

Abstract

The invention relates to the technical field of concrete materials, in particular to high-strength concrete and a preparation method thereof. The high-strength concrete is prepared from the following raw materials in parts by mass: 450 to 500 parts of cement, 160 to 200 parts of modified glass beads, 700 to 800 parts of aggregate, 200 to 250 parts of fly ash, 10 to 15 parts of calcium hydroxide, 12 to 15 parts of reinforced fibers, 8 to 12 parts of expansion filler, 8 to 12 parts of high-efficiency water reducing agent and 200 to 220 parts of water, and the reinforced fibers are prepared from steel fibers, basalt fibers and modified polypropylene fibers. The high-strength concrete shows excellent properties in multiple aspects, including improvement of mechanical properties, enhancement of durability and crack resistance, improvement of workability, improvement of self-repairing capability, reduction of temperature cracks and the like, and the high-strength concrete has wide application potential in constructional engineering due to the technical effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete materials, and in particular to a high-strength concrete and a preparation method thereof. Background Art

[0002] With the continuous development of infrastructure construction, the requirements for the performance of building materials are getting higher and higher. Although traditional concrete has been widely used in the construction field, its strength, durability and crack resistance still need to be improved. Although there are some high-strength concrete products on the market, they still have shortcomings in preparation process, cost control and material performance. Therefore, it is particularly important to develop a high-strength concrete with superior performance, simple preparation and low cost. Summary of the invention

[0003] The purpose of this application is to provide a high-strength concrete and a preparation method thereof in view of the deficiencies of current technology. The high-strength concrete prepared in this application has the advantages of simple preparation, low cost, long service life, low density, high strength, excellent durability and crack resistance, and reduced temperature cracks.

[0004] In the first aspect, the present application provides a high-strength concrete, which adopts the following technical solution: A high-strength concrete comprises the following raw materials, measured by weight: 450-500 parts of cement, 160-200 parts of modified glass microspheres, 700-800 parts of aggregates, 200-250 parts of fly ash, 10-15 parts of calcium hydroxide, 12-15 parts of reinforcing fibers, 8-12 parts of expansive fillers, 8-12 parts of high-efficiency water reducing agents, and 200-220 parts of water, wherein the reinforcing fibers consist of steel fibers, basalt fibers, and modified polypropylene fibers.

[0005] By adopting the above technical solutions, cement: as the basic cementitious material of concrete, provides basic bonding force and strength. Modified glass microspheres: increase the specific surface area and porosity, can more fully absorb other raw material components into the pores, reduce losses, and enhance the strength and retention performance of concrete. Aggregate: improve the shrinkage performance of high-strength concrete and reduce temperature cracks. Fly ash: reacts with calcium hydroxide to form CSH and CASH gels, which improve compressive strength and splitting tensile strength. Calcium hydroxide: participates in the volcanic ash reaction to enhance the strength of concrete. Reinforced fibers (steel fibers, basalt fibers and modified polypropylene fibers): improve the ductility, heat resistance, acid and alkali resistance of concrete, reduce the occurrence of cracks, and improve crack resistance and anti-seepage capabilities. Expansive fillers, using synergistic effects to improve the crack resistance and anti-seepage performance of concrete, achieve self-repair of cracks, and improve compressive strength and wear resistance. High-efficiency water reducer: reduce the water-cement ratio of concrete, improve strength and durability. Water: adjust the fluidity and workability of concrete. In summary, the present application achieves high strength, low density, excellent durability and crack resistance of high-strength concrete through the selection and proportion of specific components and modification treatment, which is particularly suitable for demanding engineering applications.

[0006] Preferably, the mass ratio of the steel fiber, basalt fiber and modified polypropylene fiber is 1:5:6, the steel fiber has a diameter of 0.2 mm and a length of 13 mm, the basalt fiber has a diameter of 14 mm and a length of 6 mm, and the modified polypropylene fiber has a diameter of 0.5 mm and a length of 15 mm.

[0007] By adopting the above technical solution, steel fiber, basalt fiber and modified polypropylene fiber are used as components of reinforcing fibers, and their specific mass ratio and physical size are designed to maximize the reinforcement effect and durability of concrete. The role of steel fiber: Steel fiber with a diameter of 0.2mm and a length of 13mm can provide good tensile strength and flexibility, which helps to withstand the internal stress of concrete during the curing and hardening process, as well as the externally applied load. Steel fiber can form a micro-reinforcement effect in concrete. When concrete is subjected to tension or pressure, the fiber can disperse these forces and reduce the formation and expansion of cracks. The role of basalt fiber: Basalt fiber with a diameter of 14mm and a length of 6mm can improve the durability of concrete in harsh environments due to its natural alkali resistance and chemical resistance. Basalt fiber has good temperature resistance and chemical stability, and can maintain its performance under various climatic conditions, thereby increasing the service life of concrete. The role of modified polypropylene fiber: Modified polypropylene fiber with a diameter of 0.5mm and a length of 15mm has enhanced bonding with concrete through special surface treatment. Modified polypropylene fibers in concrete can improve its resistance to sudden temperature changes and plastic shrinkage, and reduce cracks caused by temperature and humidity changes. Three different types and sizes of fibers work together to form a multi-level reinforcement network. Steel fibers provide strength, basalt fibers provide durability, and modified polypropylene fibers provide ductility and crack resistance. Each fiber has its own unique performance advantages, and their combination not only improves the overall performance of concrete, but also makes up for the possible performance deficiencies of a single fiber. Fibers of different diameters and lengths can more effectively disperse the stress inside the concrete, forming a more uniform and compact fiber network, thereby optimizing the structure of the concrete and improving its overall performance. In summary, this specific ratio and size of fiber mixture can significantly improve the mechanical properties and durability of concrete, making it more suitable for demanding engineering applications.

[0008] Preferably, the method for preparing the modified polypropylene fiber comprises the following steps: S31, soaking 25 parts of polypropylene fibers in 800 parts of an aqueous solution of ammonium persulfate having a mass concentration of 10 g / L, stirring for reaction for 30-40 min, filtering, washing with water until the pH value is 7, and drying to obtain activated propylene fibers; S32, according to the molar fraction, 2.5 parts of ethyl orthosilicate and 14 parts of anhydrous ethanol were mixed uniformly, and a mixture of 11 parts of deionized water and 0.2 parts of hydrochloric acid was added dropwise under stirring. After the addition was completed, the mixture was stirred and refluxed at 75° C. for 3 hours. After the sol was cooled, 5 parts of N, N-dimethylformamide with a mass concentration of 30% were added, and stirring was continued for 30-40 minutes to obtain a silica sol; S33, soaking the activated propylene fiber in the silica sol, stirring and mixing evenly, filtering, and drying to obtain modified propylene fiber.

[0009] By adopting the above technical scheme, the preparation method of modified polypropylene fiber involves several key steps, which are aimed at improving the bonding between polypropylene fiber and concrete, thereby enhancing the overall performance of concrete. The silica coating on the surface of modified polypropylene fiber can form stronger chemical and physical bonds with components such as CSH gel in concrete, thereby improving the interfacial bonding between fiber and concrete matrix. The modified polypropylene fiber is dispersed in concrete, which helps to withstand and disperse stresses caused by shrinkage, temperature changes or loads, and reduce the formation and expansion of cracks. The addition of modified polypropylene fiber also helps to improve the durability of concrete, especially in harsh environments such as low temperature or chemical erosion conditions. Due to the crack resistance of modified polypropylene fiber, the microcracks inside concrete are reduced, thereby reducing the channels for water penetration and improving the waterproof and impermeability of concrete. The modified polypropylene fiber works together with other reinforcing fibers (steel fiber and basalt fiber) to form a multi-level reinforcement network, which not only provides strength, but also provides ductility and crack resistance. This composite fiber system can prevent the formation and expansion of cracks at different scales, thereby improving the performance of concrete at the macro and micro levels. In summary, the preparation and application of modified polypropylene fibers improve the crack resistance, durability and waterproof properties of concrete by improving the bonding between the fibers and the concrete matrix, and work together with other fiber types to achieve an overall improvement in concrete performance.

[0010] Preferably, the method for preparing the modified glass microspheres comprises the following steps: S41. According to the mass proportions, 20 parts of waste glass, 5 parts of wood ash, 0.8 parts of calcium oxide, 12 parts of quartz sand and 7 parts of silica powder are added into a glass melting furnace, heated and melted at 1750° C. for 5 hours, then cooled to 1380° C. for clarification for 2 hours to obtain glass liquid, which is then quenched into cold water to obtain a glass body; S42, placing the glass body in a liquid press for high-pressure crushing to a particle size of 3-5 cm, and then using stainless steel beads as ball milling media, ball milling at a speed of 1500 rpm to obtain glass micropowder with a particle size of 130-150 mesh and a spherical surface morphology, to obtain glass microbeads; S43. According to the mass proportions, add 2 parts of γ-aminopropyl triethoxysilane to 50 parts of glass microspheres, add 300 parts of 80% ethanol-water solution, heat to 75°C and stir for 4 hours at a stirring speed of 300 rpm; then add 3 parts of isopropyl trioleyl titanate and 2 parts of Span 80, keep the speed at 700 rpm, stir for 40 minutes, then add 5 parts of polyethylene wax, stir for 2 hours at a stirring speed of 300 rpm, filter, wash and dry to obtain modified glass microspheres.

[0011] By adopting the above technical scheme, the modified glass microspheres not only improve their physical and chemical properties through a specific preparation process, but also enhance the interaction with other components of concrete, thereby improving the comprehensive performance of concrete. The surface modification is carried out by adding coupling agents such as γ-aminopropyl triethoxysilane and isopropyl trioleyl titanate, as well as Span 80 and polyethylene wax. These chemicals can form a chemical reaction layer on the surface of the glass microspheres, improving the compatibility and reactivity with organic and inorganic components in concrete. This step enhances the bonding force between the glass microspheres and concrete and improves the overall performance of concrete. The high specific surface area and porosity of the modified glass microspheres enable them to more effectively adsorb cement hydration products such as CSH gel, enhance the microstructure of concrete, and improve its compressive strength and crack resistance. The spherical glass microspheres can reduce the internal friction of concrete, improve its fluidity and pumpability, and make concrete easier to construct and shape. The surface modification layer of the modified glass microspheres can improve its chemical stability, prevent alkali-aggregate reaction in concrete, and extend the service life of concrete. Modified glass microspheres work together with other reinforcing materials (such as reinforcing fibers and expanding fillers) to form a composite reinforcement system that can improve the performance of concrete at multiple scales, from improving the pore structure of the cement matrix at the micro level to improving the mechanical strength and durability of concrete at the macro level.

[0012] Preferably, the aggregate is composed of limestone crushed stone and basalt crushed stone in a mass ratio of 5:7, and the basalt crushed stone has a water absorption rate of 1.8% and an apparent density of 2870 kg / m 3 , 5-16mm continuous graded high-strength crushed stone; the water absorption rate of the limestone crushed stone is 0.8% and the apparent density is 2720kg / m 3 , 5-16mm continuously graded high-strength crushed stone.

[0013] Preferably, the cement is P·O42.5 grade ordinary Portland cement.

[0014] Preferably, the expansion filler is composed of calcium sulphoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3.

[0015] By adopting the above technical solution, the expansion filler is composed of calcium sulfoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3. This specific ratio is to maximize the synergistic effect between the components, thereby optimizing the performance of concrete. Calcium sulfoaluminate: As an expansion agent, calcium sulfoaluminate generates ettringite when reacting with water, resulting in volume expansion, thereby compensating for the shrinkage of concrete during hardening and reducing the generation of cracks. The formation of ettringite can also improve the early strength of concrete and help to quickly form a load-bearing structure. Microsilica powder, as an ultrafine filler, can fill the tiny pores in concrete and improve the density and impermeability of concrete. After encountering water, microsilica powder can form a gel, further enhancing the internal structure of concrete, especially in cracks, helping to repair and strengthen these areas. The polymer mesh particles have a unique three-dimensional mesh structure, which can form effective water and air channels in concrete, reduce water seepage and pores, and improve the overall uniformity and durability of concrete. The polymer modified layer on its surface can be well combined with the cement matrix to improve the crack resistance and impermeability of concrete. The expansive properties of calcium sulphoaluminate combined with the pore-filling capacity of microsilica can compensate for shrinkage during the hardening of concrete, while filling microcracks caused by drying or temperature changes, working together to reduce the formation of cracks. The combination of microsilica gel and polymer mesh particles provides a dual mechanical and chemical effect, strengthening the internal structure of concrete and improving compressive strength and wear resistance. The mesh structure of the polymer mesh particles and the gel of microsilica together form a denser protective layer, improving the impermeability and durability of concrete. When cracks appear in concrete, the expansive properties of calcium sulphoaluminate and the gel of microsilica can react quickly to fill the cracks and achieve self-repair, reducing the need for external repairs and maintenance costs. The synergistic effect of these three materials not only improves the crack resistance and impermeability of concrete, but also enhances its overall mechanical properties and durability by improving the internal structure of concrete. In summary, through this specific combination of expansive fillers, the performance of concrete has been comprehensively improved, including better crack resistance, impermeability, durability and self-repair ability, making it suitable for a wider range of application scenarios, especially those projects with high requirements for concrete performance.

[0016] Preferably, the method for preparing the polymeric network particles comprises the following steps: S81, dissolving 1 part of zirconium chloride, 10 parts of maleic acid and 0.1 parts of glacial acetic acid in 350 parts of N,N-dimethylformamide according to their weight proportions, and obtaining zirconium nanoparticles through a solvothermal reaction; S82. Mix 10 parts of N-isopropylacrylamide, 1 part of sodium alginate and 0.01 part of N,N-methylenebisacrylamide according to their mass proportions, add 120 parts of deionized water, stir the mixed solution evenly at room temperature, introduce nitrogen to drive out oxygen for 30 minutes, then add 0.1 part of ammonium persulfate, add 0.2 parts of CaSO4 and 3 parts of zirconium nanoparticles under vigorous stirring, quickly pour the mixed solution into a container after stirring, and refrigerate in a refrigerator at 4-6°C; after reacting for 16 hours, soak the sample in deionized water for 36 hours, and finally pre-freeze the sample in a -35°C freeze dryer for 24 hours and dry it to obtain polymer network particles.

[0017] By adopting the above technical scheme, the preparation method of polymer mesh particles involves multiple chemical and physical steps designed to enhance their functionality in concrete. The three-dimensional network structure of polymer mesh particles can form a "micro-skeleton" inside the concrete, which helps to disperse and absorb stress caused by external loads or environmental changes, thereby reducing the formation and development of cracks. The surface and internal pores of the polymer mesh particles can effectively combine with the concrete matrix, reduce the penetration of moisture and harmful chemicals, and improve the durability and protective properties of concrete. The polymer mesh particles are evenly distributed in the concrete, which helps to improve the internal pore structure of the concrete, making it more compact, thereby improving the overall mechanical properties of the concrete. The polymer mesh particles work together with expansion fillers (such as calcium sulfoaluminate and microsilica powder) to fill cracks in the concrete through physical and chemical reactions, achieve self-repair, and extend the service life of the concrete. The synergistic effect of polymer mesh particles and other expansion fillers not only improves the crack resistance and anti-seepage performance of concrete, but also enhances the compressive strength and wear resistance of concrete, so that it can maintain good performance even in harsh environments. In summary, the polymer network particles obtained by this specific preparation method provide an effective internal reinforcement mechanism for concrete, which works together with other components such as modified glass microspheres, reinforcing fibers and expansive fillers to significantly improve the comprehensive performance of concrete.

[0018] Preferably, the high-efficiency water reducing agent is a polyhydroxy acid-based high-efficiency water reducing agent with a water reduction rate of 30%.

[0019] In a second aspect, the present application provides a method for preparing high-strength concrete, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned high-strength concrete, comprising the following steps: mixing, molding, and demolding cement, modified glass beads, aggregates, fly ash, calcium hydroxide, reinforcing fibers, expansive fillers, high-efficiency water reducing agents, and water according to their mass fractions to obtain high-strength concrete.

[0020] In summary, the beneficial technical effects of this application are: 1. Improve the mechanical properties of concrete: By increasing the specific surface area and porosity of modified glass microspheres, concrete can more fully absorb other raw material components, reduce material loss, and improve the pore structure of concrete at the microscopic level, thereby improving its compressive strength and splitting tensile strength. The volcanic ash reaction between calcium hydroxide and silica in fly ash generates CSH and CASH gel, which further improves the compressive strength of concrete.

[0021] 2. Enhance the durability and crack resistance of concrete: The addition of modified polypropylene fiber, through its good ductility and heat, acid and alkali resistance, effectively resists brittle cracks caused by plastic shrinkage and sudden temperature changes, and improves the anti-cracking properties of concrete. The three-dimensional mesh pore structure and excellent bonding properties of the polymer mesh particles significantly improve the crack resistance and anti-seepage properties of concrete, preventing cracking and water leakage.

[0022] 3. Improve the workability and impermeability of concrete: The use of high-efficiency water reducer reduces the water-cement ratio of concrete, improves the fluidity and pumpability of concrete, reduces permeability, and improves the density and durability of concrete. The addition of modified polypropylene fiber reduces the water seepage channels inside the concrete and improves the waterproof performance and impermeability.

[0023] 4. Improve the self-repairing ability and wear resistance of concrete: Calcium sulfoaluminate and microsilica powder in the expansive filler components can react quickly with water to generate ettringite and calcium hydroxide crystals, fill pores and cracks, achieve self-repair of cracks, and improve the compressive strength and wear resistance of concrete.

[0024] 5. Reduce temperature cracks and improve frost resistance: Limestone crushed stone and basalt crushed stone as aggregates can help improve the shrinkage performance of concrete and reduce cracks caused by temperature changes. Modified polypropylene fiber can help concrete relieve the internal stress caused by temperature changes, prevent the generation of tiny cracks, and improve frost resistance in low temperature environments. DETAILED DESCRIPTION

[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] Preparation Example 1 Preparation of modified polypropylene fiber The preparation method of modified polypropylene fiber comprises the following steps: S31, according to the mass fraction, immerse 25kg of polypropylene fiber in 800kg of an aqueous solution of ammonium persulfate with a mass concentration of 10g / L, stir and react for 33min, filter, rinse with water until the pH is 7, and dry to obtain activated propylene fiber; S32. According to the molar fraction, 2.5 mol of ethyl orthosilicate and 14 mol of anhydrous ethanol are mixed evenly, and a mixture of 11 mol of deionized water and 0.2 mol of hydrochloric acid is added dropwise under stirring. After the addition is completed, the mixture is refluxed at 75°C with stirring for 3 hours. After the sol is cooled, 5 mol of N,N-dimethylformamide with a mass concentration of 30% is added, and stirring is continued for 35 minutes to obtain silica sol; S33. The activated propylene fiber is immersed in the silica sol, stirred to mix evenly, filtered, and dried to obtain modified propylene fiber.

[0027] Preparation Example 2 Preparation of modified glass microspheres The preparation method of modified glass microspheres comprises the following steps: S41, according to the mass fractions, 20 kg of waste glass, 5 kg of wood ash, 0.8 kg of calcium oxide, 12 kg of quartz sand and 7 kg of silica powder were added into a glass melting furnace, heated and melted at 1750° C. for 5 h, then cooled to 1380° C. for clarification for 2 h to obtain glass liquid, which was then quenched into cold water to obtain a glass body; S42. Place the glass body into a liquid press for high-pressure crushing to a particle size of 3-5 cm, and then use stainless steel beads as ball-milling media to ball-mill at a speed of 1500 rpm to obtain glass micropowder with a particle size of 140 mesh and a spherical surface morphology to obtain glass microbeads; S43. According to the mass fraction, add 2 kg of γ-aminopropyl triethoxysilane to 50 kg of glass microbeads, add 300 kg of 80% ethanol-water solution, heat to 75°C and stir for 4 hours at a stirring speed of 300 rpm; then add 3 kg of isopropyl trioleyl titanate and 2 kg of Span 80, keep the speed at 700 rpm, stir for 40 minutes, then add 5 kg of polyethylene wax, stir for 2 hours at a stirring speed of 300 rpm, filter, wash and dry to obtain modified glass microbeads.

[0028] Preparation Example 3 Preparation of polymeric network particles The method for preparing polymeric network particles comprises the following steps: S81, dissolving 1 kg of zirconium chloride, 10 kg of succinic acid and 0.1 kg of glacial acetic acid in 350 kg of N,N-dimethylformamide according to their mass fractions, and obtaining zirconium nanoparticles by solvent thermal reaction; S82. According to the mass fractions, 10kg N-isopropylacrylamide, 1kg sodium alginate and 0.01kg N, N-methylenebisacrylamide were mixed, and 120kg deionized water was added. After the mixed solution was stirred evenly at room temperature, nitrogen was introduced to drive out oxygen for 30 minutes, and then 0.1kg ammonium persulfate was added. Under vigorous stirring, 0.2kg CaSO4 and 3kg zirconium nanoparticles were added. After stirring, the mixed solution was quickly poured into a container and refrigerated in a 5°C refrigerator. After reacting for 16 hours, the sample was immersed in deionized water for 36 hours. Finally, the sample was pre-frozen in a -35°C freeze dryer for 24 hours and dried to obtain polymer network particles.

[0029] Preparation of Comparative Example 1 Preparation of Glass Microspheres The preparation method of glass microspheres comprises the following steps: S41, according to the mass fractions, 20 kg of waste glass, 5 kg of wood ash, 0.8 kg of calcium oxide, 12 kg of quartz sand and 7 kg of silica powder were added into a glass melting furnace, heated and melted at 1750° C. for 5 h, then cooled to 1380° C. for clarification for 2 h to obtain glass liquid, which was then quenched into cold water to obtain a glass body; S42, placing the glass body in a liquid press for high-pressure crushing to a particle size of 3-5 cm, and then using stainless steel beads as ball milling media, ball milling at a rotation speed of 1500 rpm to obtain glass micropowder with a particle size of 140 mesh and a spherical surface morphology, to obtain glass microbeads.

[0030] Example 1 A high-strength concrete, calculated by mass, includes the following raw materials: 450kg cement, 160kg modified glass beads, 700kg aggregate, 200kg fly ash, 10kg calcium hydroxide, 12kg reinforcing fiber, 8kg expansive filler, 8kg high-efficiency water reducer, and 200kg water, wherein the reinforcing fiber is composed of steel fiber, basalt fiber, and modified polypropylene fiber in a mass ratio of 1:5:6. The diameter of the steel fiber is 0.2mm and the length is 13mm. The diameter of the basalt fiber is 14mm and the length is 6mm. The diameter of the modified polypropylene fiber is 0.5mm and the length is 15mm. The aggregate is composed of limestone crushed stone and basalt crushed stone in a mass ratio of 5:7. The water absorption rate of the basalt crushed stone is 1.8% and the apparent density is 2870kg / m 3 , 5-16mm continuous graded high-strength crushed stone; the water absorption rate of the limestone crushed stone is 0.8% and the apparent density is 2720kg / m 3 , 5-16mm continuously graded high-strength crushed stone, the cement is P·O42.5 grade ordinary Portland cement, the expansive filler is composed of calcium sulfoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3, and the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%.

[0031] The above-mentioned method for preparing high-strength concrete comprises the following steps: Cement, modified glass beads, aggregate, fly ash, calcium hydroxide, reinforcing fiber, expansive filler, high-efficiency water reducing agent and water are mixed, molded and demoulded according to mass proportions to obtain high-strength concrete.

[0032] Example 2 A high-strength concrete, calculated by mass, includes the following raw materials: 500kg cement, 200kg modified glass beads, 800kg aggregate, 250kg fly ash, 15kg calcium hydroxide, 15kg reinforcing fiber, 12kg expansive filler, 12kg high-efficiency water reducer, and 220kg water, wherein the reinforcing fiber is composed of steel fiber, basalt fiber, and modified polypropylene fiber in a mass ratio of 1:5:6. The diameter of the steel fiber is 0.2mm and the length is 13mm. The diameter of the basalt fiber is 14mm and the length is 6mm. The diameter of the modified polypropylene fiber is 0.5mm and the length is 15mm. The aggregate is composed of limestone crushed stone and basalt crushed stone in a mass ratio of 5:7. The water absorption rate of the basalt crushed stone is 1.8% and the apparent density is 2870kg / m 3 , 5-16mm continuous graded high-strength crushed stone; the water absorption rate of the limestone crushed stone is 0.8% and the apparent density is 2720kg / m 3 , 5-16mm continuously graded high-strength crushed stone, the cement is P·O42.5 grade ordinary Portland cement, the expansive filler is composed of calcium sulfoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3, and the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%.

[0033] The above-mentioned method for preparing high-strength concrete comprises the following steps: Cement, modified glass beads, aggregate, fly ash, calcium hydroxide, reinforcing fiber, expansive filler, high-efficiency water reducing agent and water are mixed, molded and demoulded according to mass proportions to obtain high-strength concrete.

[0034] Example 3 A high-strength concrete, calculated by mass, includes the following raw materials: 480kg cement, 180kg modified glass microspheres, 750kg aggregate, 230kg fly ash, 13kg calcium hydroxide, 14kg reinforcing fiber, 10kg expansive filler, 10kg high-efficiency water reducer, and 210kg water, wherein the reinforcing fiber is composed of steel fiber, basalt fiber, and modified polypropylene fiber in a mass ratio of 1:5:6. The diameter of the steel fiber is 0.2mm and the length is 13mm. The diameter of the basalt fiber is 14mm and the length is 6mm. The diameter of the modified polypropylene fiber is 0.5mm and the length is 15mm. The aggregate is composed of limestone crushed stone and basalt crushed stone in a mass ratio of 5:7. The water absorption rate of the basalt crushed stone is 1.8% and the apparent density is 2870kg / m 3 , 5-16mm continuous graded high-strength crushed stone; the water absorption rate of the limestone crushed stone is 0.8% and the apparent density is 2720kg / m 3 , 5-16mm continuously graded high-strength crushed stone, the cement is P·O42.5 grade ordinary Portland cement, the expansive filler is composed of calcium sulfoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3, and the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%.

[0035] The above-mentioned method for preparing high-strength concrete comprises the following steps: Cement, modified glass beads, aggregate, fly ash, calcium hydroxide, reinforcing fiber, expansive filler, high-efficiency water reducing agent and water are mixed, molded and demoulded according to mass proportions to obtain high-strength concrete.

[0036] Comparative Example 1 The same as Example 3, except that an equal amount of glass microspheres prepared in Comparative Example 1 are used instead of the modified glass microspheres.

[0037] Comparative Example 2 The same as Example 3, except that an equal amount of polypropylene fibers (0.5 mm in diameter and 15 mm in length) are used instead of modified polypropylene fibers.

[0038] Comparative Example 3 The same as Example 3, except that the expansion filler is calcium sulphoaluminate.

[0039] Comparative Example 4 The same as Example 3, except that the expansion filler is microsilica powder.

[0040] Comparative Example 5 The same as Example 3, except that the expansion filler is polymer mesh particles.

[0041] Performance Testing The high-strength concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was made into concrete specimens. The size of the concrete specimen was a cube with a side length of 100 mm. The surface was sealed with a polyethylene film and cured at room temperature for 24 hours before demolding. The specimen was moved to a standard curing box and cured to the corresponding age. The following tests were performed. The test results are shown in Table 1.

[0042] Determination of compressive strength and flexural strength: After curing for 28 days according to the specimen standard, test according to the national standard GB / T17671-2021; first observe whether the specimen has cracks, record the length of the cracks, and then test the compressive strength and flexural strength. The surface of the test block should be wiped clean before the test; Splitting strength: After 28 days of curing according to the specimen standard, the test is carried out in accordance with JTG3420-2020 "Test Procedures for Cement and Cement Concrete in Highway Engineering"; Number of freeze-thaw cycles before cracks appear: After 28 days of standard curing, the freeze-thaw cycle test was carried out in accordance with GB / T50085-2009 Test Method for Long-term Performance and Durability of Ordinary Concrete, and the number of freeze-thaw cycles corresponding to the appearance of visible cracks on the surface of the test block was recorded; The drying shrinkage performance and water resistance grade are measured according to GB / T50082-2009 "Standard for Test Methods of Long-term Properties and Durability of Ordinary Concrete" after the specimens are cured for 28 days according to the standards.

[0043] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The high-strength concrete prepared in Examples 1 to 3 has high compressive strength, flexural strength, excellent durability, crack resistance and impermeability, and reduces temperature cracks. The high-strength concrete prepared in the application has the advantages of simple preparation, low cost and long service life.

[0044] 2) The performance comparison analysis of the high-strength concrete prepared in combination with Example 3 and Comparative Example 1 shows that the modified glass microspheres of the present application not only improve their physical and chemical properties through a specific preparation process, but also enhance the interaction with other components of concrete, thereby improving the comprehensive performance of concrete. Surface modification is performed by adding coupling agents such as γ-aminopropyl triethoxysilane and isopropyl trioleyl titanate, as well as Span 80 and polyethylene wax. These chemicals can form a chemical reaction layer on the surface of the glass microspheres, improving the compatibility and reactivity with organic and inorganic components in concrete. This step enhances the bonding force between the glass microspheres and the concrete and improves the overall performance of the concrete. The high specific surface area and porosity of the modified glass microspheres enable them to more effectively adsorb cement hydration products, such as CSH gel, enhance the microstructure of concrete, and improve its compressive strength and crack resistance. The surface modification layer of the modified glass microspheres can improve their chemical stability, prevent alkali-aggregate reaction in concrete, and extend the service life of concrete.

[0045] 3) The performance comparison analysis of the high-strength concrete prepared in combination with Example 3 and Comparative Example 2 shows that the modified polypropylene fiber prepared by the present application improves the bonding force between the polypropylene fiber and the concrete, thereby enhancing the overall performance of the concrete. The silica coating on the surface of the modified polypropylene fiber can form a stronger chemical and physical bond with components such as CSH gel in the concrete, thereby improving the interfacial bonding force between the fiber and the concrete matrix. The modified polypropylene fiber is dispersed in the concrete, which helps to withstand and disperse the stress caused by shrinkage, temperature changes or loads, and reduce the formation and expansion of cracks. The addition of modified polypropylene fiber also helps to improve the durability of concrete, especially in harsh environments, such as low temperature or chemical erosion conditions. Due to the crack resistance of the modified polypropylene fiber, the microcracks inside the concrete are reduced, thereby reducing the channels for water penetration and improving the waterproof and impermeability of the concrete. The modified polypropylene fiber works together with other reinforcing fibers (steel fibers and basalt fibers) to form a multi-level reinforcement network that not only provides strength, but also provides ductility and crack resistance.

[0046] 4) The performance comparison analysis of the high-strength concrete prepared in combination with Example 3 and Comparative Examples 3-5 shows that the expansion filler is composed of calcium sulfoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:3. This specific ratio is to maximize the synergy between the components, thereby optimizing the performance of the concrete. Utilizing the synergy between them, when cracks appear in the concrete, the expansion properties of calcium sulfoaluminate and the gel of microsilica powder can react quickly, fill the cracks, achieve self-repair, and reduce the demand for external repair and maintenance costs. The synergy of these three materials not only improves the crack resistance and anti-seepage performance of the concrete, but also enhances its overall mechanical properties and durability by improving the internal structure of the concrete. Through this specific combination of expansion fillers, the performance of the concrete has been comprehensively improved, including better crack resistance, impermeability, durability and self-repair ability, making it suitable for a wider range of application scenarios, especially those projects with high requirements for concrete performance.

[0047] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A high-strength concrete, characterized in that: The preparation raw materials include the following by weight: 450-500 parts of cement, 160-200 parts of modified glass beads, 700-800 parts of aggregate, 200-250 parts of fly ash, 10-15 parts of calcium hydroxide, 12-15 parts of reinforcing fiber, 8-12 parts of expansive filler, 8-12 parts of high-efficiency water reducing agent, and 200-220 parts of water, wherein the reinforcing fiber is composed of steel fiber, basalt fiber and modified polypropylene fiber.

2. A high-strength concrete according to claim 1, characterized in that: The mass ratio of the steel fiber, basalt fiber and modified polypropylene fiber is 1:5:

6. The steel fiber has a diameter of 0.2 mm and a length of 13 mm. The basalt fiber has a diameter of 14 mm and a length of 6 mm. The modified polypropylene fiber has a diameter of 0.5 mm and a length of 15 mm.

3. The high-strength concrete according to claim 1, characterized in that: The preparation method of the modified polypropylene fiber comprises the following steps: S31, soaking 25 parts of polypropylene fibers in 800 parts of an aqueous solution of ammonium persulfate having a mass concentration of 10 g / L, stirring for reaction for 30-40 min, filtering, washing with water until the pH value is 7, and drying to obtain activated propylene fibers; S32, according to the molar fraction, 2.5 parts of ethyl orthosilicate and 14 parts of anhydrous ethanol were mixed uniformly, and a mixture of 11 parts of deionized water and 0.2 parts of hydrochloric acid was added dropwise under stirring. After the addition was completed, the mixture was stirred and refluxed at 75° C. for 3 hours. After the sol was cooled, 5 parts of N, N-dimethylformamide with a mass concentration of 30% were added, and stirring was continued for 30-40 minutes to obtain a silica sol; S33, soaking the activated propylene fiber in the silica sol, stirring and mixing evenly, filtering, and drying to obtain modified propylene fiber.

4. The high-strength concrete according to claim 1, characterized in that: The preparation method of the modified glass microspheres comprises the following steps: S41. According to the mass proportions, 20 parts of waste glass, 5 parts of wood ash, 0.8 parts of calcium oxide, 12 parts of quartz sand and 7 parts of silica powder are added into a glass melting furnace, heated and melted at 1750° C. for 5 hours, then cooled to 1380° C. for clarification for 2 hours to obtain glass liquid, which is then quenched into cold water to obtain a glass body; S42, placing the glass body in a liquid press for high-pressure crushing to a particle size of 3-5 cm, and then using stainless steel beads as ball milling media, ball milling at a speed of 1500 rpm to obtain glass micropowder with a particle size of 130-150 mesh and a spherical surface morphology, to obtain glass microbeads; S43. According to the mass proportions, add 2 parts of γ-aminopropyl triethoxysilane to 50 parts of glass microspheres, add 300 parts of 80% ethanol-water solution, heat to 75°C and stir for 4 hours at a stirring speed of 300 rpm; then add 3 parts of isopropyl trioleyl titanate and 2 parts of Span 80, keep the speed at 700 rpm, stir for 40 minutes, add 5 parts of polyethylene wax, stir for 2 hours at a stirring speed of 300 rpm, filter, wash and dry to obtain modified glass microspheres.

5. The high-strength concrete according to claim 1, characterized in that: The aggregate is composed of limestone crushed stone and basalt crushed stone in a mass ratio of 5:

7. The basalt crushed stone has a water absorption rate of 1.8% and an apparent density of 2870 kg / m 3 , 5-16mm continuous graded high-strength crushed stone; the water absorption rate of the limestone crushed stone is 0.8% and the apparent density is 2720kg / m 3 , 5-16mm continuously graded high-strength crushed stone.

6. The high-strength concrete according to claim 1, characterized in that: The cement is ordinary Portland cement of grade P·O42.

5.

7. The high-strength concrete according to claim 1, characterized in that: The expansion filler is composed of calcium sulphoaluminate, microsilica powder and polymer mesh particles in a mass ratio of 1:1:

3.

8. The high-strength concrete according to claim 7, characterized in that: The method for preparing the polymeric network particles comprises the following steps: S81, dissolving 1 part of zirconium chloride, 10 parts of maleic acid and 0.1 parts of glacial acetic acid in 350 parts of N,N-dimethylformamide according to their weight proportions, and obtaining zirconium nanoparticles through a solvothermal reaction; S82. Mix 10 parts of N-isopropylacrylamide, 1 part of sodium alginate and 0.01 part of N,N-methylenebisacrylamide according to their mass proportions, add 120 parts of deionized water, stir the mixed solution evenly at room temperature, introduce nitrogen to drive out oxygen for 30 minutes, then add 0.1 part of ammonium persulfate, add 0.2 parts of CaSO4 and 3 parts of zirconium nanoparticles under vigorous stirring, quickly pour the mixed solution into a container after stirring, and refrigerate in a refrigerator at 4-6°C; after reacting for 16 hours, soak the sample in deionized water for 36 hours, and finally pre-freeze the sample in a -35°C freeze dryer for 24 hours and dry it to obtain polymer network particles.

9. The high-strength concrete according to claim 1, characterized in that: The high-efficiency water reducing agent is a polyhydroxy acid-based high-efficiency water reducing agent with a water reduction rate of 30%.

10. A method for preparing a high-strength concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Cement, modified glass beads, aggregate, fly ash, calcium hydroxide, reinforcing fiber, expansive filler, high-efficiency water reducing agent and water are mixed, molded and demoulded according to mass proportions to obtain high-strength concrete.

Citation Information

Cited By

  • High-toughness ultra-high performance concrete and preparation method thereof

    CN120097688A

  • High-toughness ultra-high performance concrete and preparation method thereof

    CN120097688B